Happle–Tinschert, Curry–Jones and segmental basal cell naevus syndromes, overlapping disorders caused by somatic mutations in hedgehog signalling genes: the mosaic hedgehog spectrum. (1st January 2020) - Lovgren, M.‐L.; Zhou, Y.; Hrčková, G.; Dallos, T.; Colmenero, I.; Twigg, S.R.F.; Moss, C.
Abstract : Summary: Happle–Tinschert syndrome (HTS) and Curry–Jones syndrome (CJS; OMIM 601707) are rare, sporadic, multisystem disorders characterized by hypo‐ and hyperpigmented skin patches following Blaschko's lines, plus acral skeletal and other abnormalities. The blaschkoid pattern implies mosaicism, and indeed CJS was found in 2016 to be caused by a recurrent postzygotic mutation in a gene of the hedgehog signalling pathway, namely SMO, c.1234C>T, p.Leu412Phe. More recently the original case of HTS was found to carry the same somatic mutation. Despite this genetic and phenotypic overlap, two significant differences remained between the two syndromes. The histological hallmark of HTS, basaloid follicular hamartomas, is not a feature of CJS. Meanwhile, the severe gastrointestinal manifestations regularly reported in CJS had not been described in HTS. We report a patient whose phenotype was entirely consistent with HTS apart from intractable constipation, and a second patient with classic features of CJS plus early‐onset medulloblastoma, a feature of basal cell naevus syndrome (BCNS). Both had the same recurrent SMO mutation. This prompted a literature review that revealed a case with the same somatic mutation, with basaloid follicular hamartomas and other features of both CJS and BCNS. Segmental BCNS can also be caused by a somatic mutation in PTCH1 . We thus demonstrate for the first time phenotypic and genetic overlap between HTS, CJS and segmental BCNS. All of these conditions are caused by somatic mutations in genes of the hedgehog signalling pathway and we therefore propose the unifying term 'mosaic hedgehog spectrum'. What's already known about this topic? Happle–Tinschert syndrome (HTS) and Curry–Jones syndrome (CJS) are rare mosaic multisystem disorders with linear skin lesions. CJS is characterized by severe constipation, which has not previously been reported in HTS. HTS is characterized by basaloid follicular hamartomas, which are not a recognized feature of CJS. The recurrent mosaic SMO mutation found in CJS was recently reported in a patient with HTS. What does this study add? We describe a patient with HTS and intractable constipation, and a case of CJS with medulloblastoma. Both patients had the same recurrent somatic SMO mutation also found in a case reported as segmental basal cell naevus syndrome. SMO functions in the hedgehog pathway, explaining phenotypic overlap between HTS, CJS and mosaic basal cell naevus syndrome. We propose the term 'mosaic hedgehog spectrum' for these overlapping conditions.